REPRESENTATION OF INDONESIAN’S BEAUTY CONCEPT IN “CITRA” HAND & BODY LOTION ADVERTISEMENT USING ROLAND BARTHES’ SEMIOTICS APPROACH - Kurniawan, Yulius; Putra, Yosua Ade; Fadilah, Eka (Universitas Negeri Surabaya, 2024)
This study explores the representation of beauty concept in Indonesian advertisements, with a focus on Citra's